Ventricular Tachycardia Storm Originating From Moderator Band Requiring Extracorporeal Membrane Oxygenation - Darden, Douglas (JACC Case Rep, 2020)
A 67-year-old man presented with dizziness secondary to ventricular tachycardia (VT) originating from the moderator band. The VT was refractory to multiple antiarrhythmic medications requiring extracorporeal membrane oxygenation and eventual curative ablation. We highlight a malignant form of idiopathic VT, unique electrocardiogram characteristics, and ablation considerations. (Level of Difficulty: Intermediate.)